GIVETIAN–FRASNIAN BOUNDARY CONODONTS FROM KERMAN PROVINCE, CENTRAL IRAN - HOSSEIN GHOLAMALIAN; VACHIK HAIRAPETIAN; NAHID BARFEHEI; SOHEYLA MANGELIAN; PARVANEH FARIDI (Rivista Italiana di Paleontologia e Stratigrafia, 2013)
The Middle - Late Devonian boundary is investigated based on twenty-two conodont species and subspecies from three sections in the north and west of Kerman, southeastern central Iran. Upper Givetian - lower Frasnian carbonates of the basal part of the Bahram Formation transgressively overlie the sandstone beds of the top of (?) Early - Middle Devonian Padeha Formation. These massive skeletal limestones encompass the G-F boundary. The base of Frasnian is identified by the appearance of early forms of Ancyrodella rotundiloba . It helps to compare our biozones to those of global stratotype in southern France. A new species, Polygnathus hojedki n. sp. is described here. New range is suggested for P. praepolitus .